IgG4-Related Inflammatory Pseudotumor of the Trigeminal Nerve: Another Component of IgG4-Related Sclerosing Disease? - Katsura, M. (AJNR Am J Neuroradiol, 2011)
IgG4-related IPTs have been reported in various sites and may form part of the spectrum of systemic IgG4-related sclerosing disease. Some pseudotumors are clinically and radiologically indistinguishable from malignant tumors. We present the first case of an IgG4-related IPT of the trigeminal nerve diagnosed histopathologically without involvement of any of the common sites. The trigeminal nerve pseudotumor may represent a component of IgG4-related sclerosing disease.